Bemerkungen zum Formalisierungsproblem in der Linguistik - Koniuszaniec, Gabriela (Studia Germanica Posnaniensia, 2018)
The author considers the advantages and shortcomings of formalization applied in modern linguistics, especially in taxonomic and generative syntax. The author emphasizes the cognitive and audio-visual values of graphs of a type of binary tree diagram and the lack of such values in non-binary dependent trees. The usefulness of scalar schemes and the formulas of the logic of predicate are also mentioned.